2022
DOI: 10.3390/land11020312
|View full text |Cite
|
Sign up to set email alerts
|

The Perception of the Vertical Dimension (3D) through the Lens of Different Stakeholders in the Property Market of China

Abstract: China has experienced fast urbanization with a growing urban population, which has inevitably led to the adoption of a vertical housing style with high-rise buildings. However, how people subjectively perceive the vertical dimension (3D) in the property market is neither adequately documented nor well understood. The 3D perception helps us to understand a myriad of social and psychological effects of living in high-rise buildings. We organized and conducted semi-structured expert interviews, focus groups, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…In Zhao, Liu [20], noise distribution had a clear impact: the closer the proximity to the road, the higher the concentration; the higher the storey level, the lower the concentration. Ying, Koeva [8] confirmed that people had diverse 3D housing preferences, e.g., more people preferred to live at a high-storey level in a high-rise residential building. In analogy, air quality also partially depended on the 3D building configuration [67].…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…In Zhao, Liu [20], noise distribution had a clear impact: the closer the proximity to the road, the higher the concentration; the higher the storey level, the lower the concentration. Ying, Koeva [8] confirmed that people had diverse 3D housing preferences, e.g., more people preferred to live at a high-storey level in a high-rise residential building. In analogy, air quality also partially depended on the 3D building configuration [67].…”
mentioning
confidence: 86%
“…VR aims to create immersive environments for buyers and facilitate their understanding of the indoor and outdoor environments of the properties [53]. Current works have, on one hand, suggested VR plays an important role in housing purchase decision-making [54,55]; on the other hand, its usefulness in a flourishing housing market, the credibility to reflect reality, and the high cost were questioned as well [8]. The potential of VR rather than visualisation only deserves to be further explored.…”
Section: The Relevant Research Of 3dpvmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a dearth of empirical work exploring such relationships in the context of China. A survey conducted by Ying et al (2022) revealed that Chinese house buyers highly valued the three-dimensional factors of neighbourhoods, but it seems that local authorities and real estate developers have not yet emphasised these elements. Detailed analysis on how horizontal and vertical land-use configuration in immediate and broader neighbourhoods is related to property value remains scarce; this study addresses this research gap.…”
Section: Neighbourhood Characteristics and Property Valuementioning
confidence: 99%